Luxury product and brand purchasing behavior: Introduction to a Journal of Global Scholars of Marketing Science (JGSMS) special section - Correia, Antónia (2021)
Over the recent years, there has been a steady increase in the number of customers in luxury market. Such a substantial rise has gained much attention from both academics and industry experts seeking to better understand the meanings and factors involved in luxury consumption. Therefore, this special section aims to enrich and update the existing body of knowledge on luxury product and brand purchasing behaviour. We have encouraged the contributors to forward both conceptual and empirical papers reflecting current concerns in the field of luxury shopping, more specifically in luxury product and brand purchasing behaviour. In the end, this special section includes three papers on external store environment, meaning of luxury, and luxury brand fashion. Certainly, additional references are necessary for better understanding the meaning and contents of luxury consumption and main drivers behind it. The special section introduces the reader to some of these important references but also notes that there is still avenue for more studies in the future.